Effect of Covid-19 on Public Transport Commuters’ Well-Being in Ilorin Metropolis, Nigeria (Lapai Journal of Economics, 2020)
COVID-19 outbreak is a pandemic that shakes the whole world without exception. The pandemic has caused a lot of activities to stop, with strict restriction on mobility in order to curtail the spread of the virus. The transport sector is one of the most affected sectors in the economy. This study therefore, investigates the impact of COVID-19 Pandemic on public transport commuters’ wellbeing in Ilorin metropolis of Kwara State Nigeria through cross-sectional survey technique. Questionnaire was used to 117 respondents who were selected using convenient sampling techniques. PLS-SEM path modeling was employed to process the data.  The result revealed that the major determinants of public transport commuter’s well-being during the first wave of COVID-19 pandemic in Nigeria are quality of road and transport fare. The study therefore recommended the need for improvement in quality of road by the government and provision of alternative means of transportation like railway for public transport commuters.